Applications of Abraham solvation parameter model: estimation of the lethal median molar concentration of the antiepileptic drug levetiracetam towards aquatic organisms from measured solubility data. (3rd May 2020) - Yue, David; Acree, William E.; Abraham, Michael H.
ABSTRACT: Abraham model solute descriptors are calculated for the pharmaceutical compound levetiracetam based on experimental solubility data retrieved from the published literature. The calculated solute descriptors mathematically describe the solubility behaviour of levetiracetam in methanol, ethanol, 1-propanol, 2-propanol, acetone, acetonitrile, ethyl acetate, toluene and cyclohexane to within a standard error of 0.102 log units. Once calculated the Abraham model solute descriptors can be used to estimate the solubility of levetiracetam in more than 100 different organic solvents, as well as several important environmental and pharmaceutical properties, such as the lethal median molar concentration of levetiracetam towards various aquatic organisms and blood-to-body organ (or tissue) partition coefficients.